Designing and Evaluating the User Interface of a Socratic Dialogue Chatbot to Enhance Student Engagement in Online Learning Platforms - Widjanarko, Alexander; Haq, Isri Amirul; Mubarok, Berlian Davis Dwi; Purnawirawan, Okta (Journal of Information Technology and Computer Science, 2026)
History education in Phase F is often perceived as monotonous and dominated by rote memorization, with 92.9% of students feeling burdened and 89.3% feeling bored. Standard generative AI tools may worsen this issue by functioning as instant answering machines, fostering cognitive dependency. This study aims to describe the User Interface (UI) and User Experience (UX) design process of “Kak Sarah,” a Learning Management System (LMS) platform featuring a chatbot designed to act as a Socratic facilitator through historical role-play, and to evaluate its usability and impact on student engagement. The UI/UX development employed the Successive Approximation Model (SAM) integrated with the Design Thinking approach, consisting of empathize, define, ideate, prototype, and test stages. The platform’s usability was evaluated using the System Usability Scale (SUS) with 136 respondents, while its impact on engagement was tested on 312 Grade XI students across five high schools. Results indicate that the UI design successfully translated four narrative learning stages into an interactive interface. The usability evaluation produced a SUS score of 86.09 (Excellent / Grade A). Observation data and conversation logs showed that all students engaged in reflective thinking rather than accepting direct answers, supported by a 35.03-point increase in critical thinking scores (p = 0.005). These findings suggest that integrating SAM and Design Thinking can produce an effective Socratic chatbot interface that enhances student engagement in history learning.